Health behaviours in ambulance workers. (2nd September 2020) - Hutchinson, Lucy Catherine; Forshaw, Mark J; Poole, Helen
Abstract : Introduction: Awareness is increasing that health behaviours, which are a part of a person's lifestyle, have significant effects on emotional and physical wellbeing. Ambulance workers are at a higher risk of poorer psychological health outcomes than the general population. This begs the question whether lifestyle could play a role in emotional and physical health outcomes, which is an understudied area in this population. This paper reviews health behaviours in paramedics and assesses the impact they may have on their emotional and physical wellbeing. Methodology: PRISMA guidelines were adhered to and seven online bibliographic databases (MEDLINE, CINAHL, PsychArticles, PsychINFO, Web of Science, PubMed and Google Scholar) and reference lists of eligible articles were searched. Papers were systematically extracted and selected by title, then by abstract using inclusion and exclusion criteria. Findings: The papers included in this review (n=6) cover a range lifestyle factors (physical activity, smoking, alcohol use and sleep) that potentially affect wellbeing outcomes (weight/body mass index and post-traumatic stress symptoms) of ambulance workers across the Western world. They have various limitations. Conclusion: Ambulance workers engage in negative health behaviours that have some bearing on their emotional and physical wellbeing. Further research could explore the role of health behaviours and lifestyle in ambulance workers using validated measures. The findings could support the development of an evidence-based, occupation-specific intervention.